Meningkatkan Hasil Belajar Siswa pada Materi Persamaan Kuadrat Melalui Penerapan Model Problem Based Learning - Kadek Savitri; Muh Rizal; Linawati Linawati (Universitas Tadulako, 2021)
The purpose of this study was to obtain a description of the application of the Problem Based Learning model that can improve student learning outcomes in Quadratic Equations Class X of IPA 4 SMA N 1 Torue. The type of research used is classroom action research (CAR) which refers to the research design of Kemmis and Mc. Taggart, namely: planning, action, observation, and reflection. The research has been carried out, obtained that the learning outcomes of class X IPA 4 Torue 1 Senior High School in the quadratic equation material has increased, namely the results of observation of teacher and student activities in the first cycle are in the good category while in the second cycle the observations of the activities of teachers and students are in the very good category. In the first cycle the percentage of classical completeness was 47.2% while the second cycle of the classical completeness percentage was 77.27%. Based on these results, it can be concluded that the application of the PBL model can improve student learning outcomes in the quadratic equation material in class X IPA 4 Torue 1 SMA by following the phases as follows: (1) Student orientation to the problem, (2) Organizing students to learning, (3) guiding individual and group investigations, (4) developing and presenting work, and (5) analyzing and evaluating problem solving processes.